Form & symbolism of rings from Perbadanan Adat Melayu dan Warisan Negeri Selangor / Nur Amalina Khairul Annuar, Arba’iyah Ab. Aziz and Mohamad Kamal Abd. Aziz - Khairul Annuar, Nur Amalina; Ab. Aziz, Arba’iyah; Abd. Aziz, Mohamad Kamal (Faculty of Art and Design, 2022)
A ring is regarded as part of jewellery, material culture, or artefact that carries beliefs, values, concepts, and the identity of a civilization. Therefore, it has enormous societal importance and is regarded as a symbol of national heritage art. Although they have been around and existed in Malaysia for a long time, as well as being kept and displayed in museums as national treasures, however, it is still a challenge to obtain a source of reference for detailed information connected to jewellery owing to a lack of reading resources. This study aims to examine and document the form and symbolism of rings from Perbadanan Adat Melayu Dan Warisan Negeri Selangor (PADAT) collection. The findings from this study will be able to contribute in-depth insights on rings as a source of reference and guidance for future needs for jewellers, designers, scholars, the public, researchers, including other related disciplines, and the young generation while preserving the traditional values and simultaneously promoting the aesthetic appreciation. Focusing on five rings from PADAT, this study describes the various characteristics of ring form based on multiple elements such as motif and material, as well as its relation to the symbolic meaning, employing the theory of Ferdinand de Saussure of Semiotics.